Pertanggungjawaban Pidana Penipuan Oleh Pengurus Koperasi Simpan Pinjam Amanah Ray Mandiri - Hasibuan, Debby Kartika; Marsella, Marsella; Sitorus, Nanang Tomi (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
Currently, the phenomenon of fraud committed by cooperatives in collecting public funds is increasingly widespread, especially in the case of Amanah Ray Mandiri savings and loan cooperative. This study aims to determine the legal provisions related to credit cooperatives in raising public funds, as well as to determine the criminal liability of the Amanah Ray Mandiri credit cooperative management based on Decision No. 1839/Pid. PN.Mdn. This research method uses normative juridical research with secondary data obtained through library research. The results showed that the criminal liability of the director of the Amanah Ray Mandiri savings and loan cooperative based on Decision No. 1839/Pid.B/2020/PN.Mdn, where the panel of judges used Article 378 of the Criminal Code to impose imprisonment on the perpetrator. Sentenced to 2 years in prison in accordance with applicable legal provisions. Law No. 17 of 2012 related to cooperatives does not regulate criminal liability that can be imposed on cooperative administrators who commit criminal acts of fraud, there are only administrative sanctions, therefore, as long as the operating law does not regulate criminal liability, the provisions in the Criminal Code (KUHP) can be applied.